Shear Strength Models for Reinforced Concrete Slender Beams: Comparative Analysis and Parametric Evaluation - Cailong Ma; Zheyi Guo; Wenhu Wang; Yongjun Qin (Buildings, 2022)
Shear failure of reinforced concrete (RC) members belongs to brittle failure and has always been concerned. In this paper, 16 existing shear strength models of RC slender beams have been selected and comprehensively compared based on a set of 781 experimental test results. These formulas from eight national codes and eight published papers are mainly the semi-empirical models or the analytical models. These experimental test results were collected from 66 published papers, and the range of key parameters is relatively wide. The accuracy of these shear strength models is evaluated from overall prediction level and the effect of key parameters. These key parameters mainly contain concrete compressive strength, shear-span-to-depth ratio, effective depth, and stirrup ratio. According to the results of overall prediction and evaluation of key parameters, the prediction results of Zsutty’s, Gunawan’s, and Bazant–Kim’s models are more accurate than others for both beams with stirrups and without stirrups. The models of ACI and JSCE exhibit higher prediction accuracy and safety margin, and their average values are between 1.19 and 1.28. The results of this study may provide reference for the selection and/or improvement of the shear strength model for RC slender beams.